Sign System in Sport and Leisure Facility: A Study Case of Bandung Giri Gahana Golf & Resort - Prima, Rizky Arie; Swasty, Wirania (Universitas Ciputra, 2017)
Sign systems are presented in sign programs in which there is information as well as navigation for visitors to a destination. This paper is a case study of Bandung Giri Gahana Golf and Resort as one of the sport and leisure facilities in Bandung. The identified problem is that the signage does not have a single unified / clear system. In this case study, the methods used in data collection consist of observation, interviews, and literature study. For the analysis method using matrix analysis. The sign system design is made to add visual attractiveness that is presented to the visitors, to beautify the facility area location and to assist the visitors in finding the facilities in the area. The purpose of this study is to create a sign system as an informative and effective visual communication to local and foreign visitors, as well as to provide a visual appeal to increase brand awareness.